Analysis of CO2 Concentration and Fluxes of Lisbon Portugal Using Regional CO2 Assimilation Method Based on WRF-Chem - Jiuping Jin; Yongjian Huang; Chong Wei; Xinping Wang; Xiaojun Xu; Qianrong Gu; Mingquan Wang (Atmosphere, 2025)
Cities house more than half of the world’s population and are responsible for more than 70% of the world anthropogenic CO2 emissions. Therefore, quantifications of emissions from major cities, which are only less than a hundred intense emitting spots across the globe, should allow us to monitor changes in global fossil fuel CO2 emissions in an independent, objective way. The study adopted a high-spatiotemporal-resolution regional assimilation method using satellite observation data and atmospheric transport model WRF-Chem/DART to assimilate CO2 concentration and fluxes in Lisbon, a major city in Portugal. It is based on Zhang’s assimilation method, combined OCO-2 XCO2 retrieval data, ODIAC 1 km anthropogenic CO2 emissions and Ensemble Adjustment Kalman Filter Assimilation. By employing three two-way nested domains in WRF-Chem, we refined the spatial resolution of the CO2 concentrations and fluxes over Lisbon to 3 km. The spatiotemporal distribution characteristics and main driving factors of CO2 concentrations and fluxes in Lisbon and its surrounding cities and countries were analyzed in March 2020, during the period affected by COVID-19 pandemic. The results showed that the monthly average CO2 and XCO2 concentrations in Lisbon were 420.66 ppm and 413.88 ppm, respectively, and the total flux was 0.50 Tg CO2. From a wider perspective, the findings provide a scientific foundation for urban carbon emission management and policy-making.